Development of a Food-Exchange Model to Replace Saturated Fat with MUFAs and n–6 PUFAs in Adults at Moderate Cardiovascular Risk. Issue 6 (9th April 2014) - Weech, Michelle; Vafeiadou, Katerina; Hasaj, Marinela; Todd, Susan; Yaqoob, Parveen; Jackson, Kim G.; Lovegrove, Julie A.
Abstract: The recommendation to reduce saturated fatty acid (SFA) consumption to ≤10% of total energy (%TE) is a key public health target aimed at lowering cardiovascular disease (CVD) risk. Replacement of SFA with unsaturated fats may provide greater benefit than replacement with carbohydrates, yet the optimal type of fat is unclear. The aim of the DIVAS (Dietary Intervention and Vascular Function) study was to develop a flexible food-exchange model to investigate the effects of substituting SFAs with monounsaturated fatty acids (MUFAs) or n–6 (ω-6) polyunsaturated fatty acids (PUFAs) on CVD risk factors. In this parallel study, UK adults aged 21–60 y with moderate CVD risk (50% greater than the population mean) were identified using a risk assessment tool ( n = 195; 56% females). Three 16-wk isoenergetic diets of specific fatty acid (FA) composition (%TE SFA:%TE MUFA:%TE n–6 PUFA) were designed using spreads, oils, dairy products, and snacks as follows: 1 ) SFA-rich diet (17:11:4; n = 65); 2 ) MUFA-rich diet (9:19:4; n = 64); and 3 ) n–6 PUFA-rich diet (9:13:10; n = 66). Each diet provided 36%TE total fat. Dietary targets were broadly met for all intervention groups, reaching 17.6 ± 0.4%TE SFA, 18.5 ± 0.3%TE MUFA, and 10.4 ± 0.3%TE n–6 PUFA in the respective diets, with significant overall diet effects for the changes in SFAs, MUFAs, and n–6 PUFAs between groups ( P < 0.001). There were no differences in the changes of total fat, protein, carbohydrate, and alcohol intake or anthropometric measures between groups. Plasma phospholipid FA composition showed changes from baseline in the proportions of total SFAs, MUFAs, and n–6 PUFAs for each diet group, with the changes in SFAs and MUFAs differing between the groups ( P < 0.001). In conclusion, successful implementation of the food-exchange model broadly achieved the dietary target intakes for the exchange of SFAs with MUFAs or n–6 PUFAs with minimal disruption to the overall diet in a free-living population. This trial was registered at clinicaltrials.gov as NCT01478958.